Answer:
B) π
Step-by-step explanation:
y = sin 2 (x – π∕2)
y = sin (2x -π)
=> 2x = 2π
x = π
Answer:
no it does not have to
Step-by-step explanation:
Answer:
x = 46
Step-by-step explanation:
Since the angles are equal to each other, make the equations equal to each other.
4x - 36 = 3x + 10 and simplify
x - 36 = 10
x = 46
Hope this helps!
(-2 = √x - 7)x² (calculate)
(-9 = √x)x² (remove the parantheses)
-9x² + √x x²
Answer:
3 times 4 + 5 = 17
Step-by-step explanation:
3d+5=17
-5 -5
________
3d = 12
__ __
3 3
d = 4